Sugar and Salt in a Young Child’s Diet: Effect on Health - Vera A. Skvortsova; Tatiana E. Borovik; Natalia N. Semenova; Tatiana V. Bushueva; Elena A. Roslavtseva; Tatiana N. Stepanova; Irina M. Guseva; Malohat V. Khodzhieva (Вопросы современной педиатрии, 2016)
Salt and sugar are traditional components of a daily diet for both adults and children. These flavor additives have been used by human for centuries. Sugar and salt not only enhance the taste of food, but also play an important role in metabolic processes. We have already accumulated some data on long-term adverse effects related to excessive consumption of salt and sugar. However, the need for sodium and sucrose has not been finally established yet. We anticipate the reduction in sugar consumption rates. Daily intake of salt and sugar can be optimized by forming proper eating habits in early childhood, with a particular focus on complementary foods free of nutritional supplements, which is necessary for an adequate development of taste.